Language and ethnicity in minority sociolinguistic perspective / Joshua A. Fishman - Fishman, Joshua A. (Estados Unidos de América : Multilingual matters, 1989)
Este libro se trata sobre lenguaje y etnicidad en minoría sociolingüística
Incluye índice y bibliografía
Col. Soc
Keywords: 1. ANTHROPOLOGICAL LINGUISTICS 2. ETHNIC GROUPS